The Effectiveness of the Combination of Basil Leaf Decoction and the Health Belief Model in Preventing Pathological Vaginal Discharge among Women of Reproductive Age - Purba, Anita Gandaria (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Pathological vaginal discharge is caused by infections from pathogens such as Trichomonas vaginalis, Candida species, Chlamydia trachomatis, and Neisseria gonorrhoeae. Pathological vaginal discharge can cause discomfort, and if left untreated for a long time, it may lead to pelvic inflammatory disease, infertility, and cervical cancer. The Health Belief Model (HBM) is the most commonly used model to guide individuals toward engaging in preventive health behaviors. The application of HBM in preventing pathological vaginal discharge is important because it helps increase awareness and promote preventive behaviors. The use of natural ingredients to address pathological vaginal discharge is becoming more familiar among the community compared to synthetic products due to their safety and affordability.Research Objectives: To analyze the effectiveness of basil leaf decoction, evaluate the influence of HBM on preventing pathological vaginal discharge, and determine the effectiveness of the combination of basil leaf decoction and HBM.Methods: This study employed a quasi-experimental design with a pre-test and post-test control group conducted in Lubuk Pakam village. Respondents were divided into three groups with a total sample size of 150 individuals.Results: Pre-test results showed that initial scores were almost the same across all groups, indicating no significant differences before the intervention. After six weeks, the basil decoction group showed a 24.6% improvement in preventive behavior, the HBM group showed a 33.4% increase, and the combination group showed a 45.7% increase. These findings indicate that the combination of basil leaf decoction and HBM education is more effective than single interventions.The HBM model proved effective in enhancing awareness and preventive behavior, especially when combined with biological intervention such as basil leaf decoction. This combination produced a synergistic effect that encouraged higher compliance and stronger behavioral change compared to single interventions.The combination of basil leaf decoction and education based on the Health Belief Model (HBM) was found to be the most effective in improving preventive behaviors against pathological vaginal discharge in women of reproductive age compared to single interventions. This intervention significantly increased knowledge, perception, and motivation to carry out preventive actions. Therefore, this combined biological and educational approach is recommended for widespread implementation in women's reproductive health programs.